EMP characterization at PALS on solid-target experiments. (23rd August 2018) - Consoli, F; De Angelis, R; De Marco, M; Krasa, J; Cikhardt, J; Pfeifer, M; Margarone, D; Klir, D; Dudzak, R
Abstract: We describe the characterization of electromagnetic pulses (EMPs) in experiments on solid targets at PALS laser facility in Prague, for energy up to 600 J and intensity up to 10 16 W cm −2 at focus. Measurements of EMPs have been performed by different conductive probes placed inside and outside the experimental chamber. We show results for different targets and probe configurations, and illustrate effects of spurious direct coupling of these transient fields with the read-out apparatus, which are important for high-energy and high-intensity laser-plasma experiments. The related countermeasures are described and demonstrated to be very effective for improving the signal-to-noise ratio, at expenses of measured bandwidths. They allowed us to detect the EMP components due to the intense neutralization currents flowing through the target holder, and those possibly due to wakefields associated with emitted charged particles, which resulted in these experiments to be of the same order of magnitude. It is the first time both discharge current and associated EMP are effectively measured in the same nanosecond-scale experiment, where this EMP contribution is effectively detected by conductive probes. A remarkable agreement was obtained from comparison of the detected EMP profile with measured neutralization current. We also show the results achieved by means of electromagnetic simulations of fields in the modeled experimental chamber, in particular in the regions where the probes were actually placed during the experiments, and compare them with measured signals. It appears that conductive probes have limitations for the measurement of the high-frequency components of the EMP fields. The illustrated results are of primary importance for the hot topic of EMP characterization and minimization in plants for inertial-confinement-fusion (NIF, LMJ, PETAL) as well as for laser-plasma acceleration (PETAL, ELI, Apollon…).